The diagnostic and cellularity yield of reverse bevel versus fork‐tip fine needle biopsy. Issue 8 (7th May 2018) - Abdelfatah, Mohamed M; Hamed, Ahmed; Koutlas, Nicholas J.; Aly, F. Zahra
Abstract : Introduction: Two new systems with a novel tip (Procore™ and SharkCore™) have been introduced for ultrasound‐guided fine needle biopsy (US‐FNB). Direct comparison of the diagnostic yield of these needles in the evaluation of pancreatic lesions is currently under investigation. This study aims to compare the diagnostic and cellular yields of the two needle systems. Methods: Consecutive patients with upper gastrointestinal lesions undergoing EUS‐FNB using 22 gauge Procore™ (reverse bevel) or SharkCore™ (fork‐tip) needles were included in the study. Cytological rapid on‐site evaluation (ROSE) slides were scored on a numerical scale of diagnostic yield relative to the number of passes. Similarly, histology of biopsy material was assessed on diagnostic quality using a numeric score. The final diagnosis was based on resection specimens and/or follow‐up of clinical and imaging data of the subject. Results: The diagnostic yield was similar between the fork‐tip and reverse bevel needles (125/163; 77% vs 103/139;74% with P  = .60). Sub‐analysis for solid pancreatic masses demonstrated similar results (69/88; 78% vs. 83/107; 78% with P  = .88). The fork‐tip needle had a lower mean number of passes (2.5 vs 3.1; P  = .04) and ROSE was utilized in significantly less cases than in the reverse bevel needle group (77% versus 98.3%). Conclusions: Although we observed no difference in the diagnostic yield using either the fork‐tip or the reverse bevel needle, the fork‐tip needle had significantly better performance with regards to achieving more adequate cytologic specimen in fewer number of passes while at the same time requiring fewer episodes of ROSE.